KONSEP PENDIDIKAN ISLAM DALAM PERSPEKTIF IBNU SINA - Maidar Darwis (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2013)
Nowadays, our national educational system has adopted theories of education from western, meanwhile, theories of Islamic education have been neglected. People even do not know which theories are coming from western and which ones are from Islam. Yet, there are some basic differences between both. Therefore, it is necessary to investigate about philosophers’ point of view toward concept of education. One of it is the concept of education from Ibnu Sina. His concept about education can be explained from the goal, material, method, teachers and punishment. Basically his concept is still actual and relevant to today’s development of modern education.